1988
DOI: 10.1128/jb.170.9.4194-4208.1988
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence and transcriptional analysis of the spo0F region of the Bacillus subtilis chromosome

Abstract: The total sequence of a 6,314-base-pair BgllM fragment of the BaciUus subtiUs chromosome containing the spoOF locus has been accomplished. Several genes of interest have been identified on this DNA fragment. The ctrA locus was recognized as coding for CTP synthetase by comparison of its deduced sequence with that of Escherichia coli CTP synthetase. A total of 53% of the residues are identical between the enzymes from these organisms. The spoOF locus was followed immediately by a locus, tsr, required for RNA sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…The amount of protein recovered in each sample was determined by amino acid analyses performed in duplicate (Packman & Berry, 1995). , 1989), Campylobacter jejuni (Burucoa et al, 1995), Schizosaccharomycespombe (Mutoh & Hayashi, 1994), Saccharomyces cerevisiue (Schwelberger et al, 1989), Neurospora crassa (Yamashita & Stuart, 1995), Corynebacterium glutamicum (von der Osten et al, 1989), Bacillussubtilis (Trach et al, 1988;Mitchell et al, 1992). and Rhodobactersphaeroides (Chen et al, 1991;Gibson et al, 1991) were aligned using the computer program PILEUP (Devereux et al, 1984) with a gap weight of 3.0and a gap length weight of 0.1.…”
Section: Sequence Alignmentsmentioning
confidence: 99%
“…The amount of protein recovered in each sample was determined by amino acid analyses performed in duplicate (Packman & Berry, 1995). , 1989), Campylobacter jejuni (Burucoa et al, 1995), Schizosaccharomycespombe (Mutoh & Hayashi, 1994), Saccharomyces cerevisiue (Schwelberger et al, 1989), Neurospora crassa (Yamashita & Stuart, 1995), Corynebacterium glutamicum (von der Osten et al, 1989), Bacillussubtilis (Trach et al, 1988;Mitchell et al, 1992). and Rhodobactersphaeroides (Chen et al, 1991;Gibson et al, 1991) were aligned using the computer program PILEUP (Devereux et al, 1984) with a gap weight of 3.0and a gap length weight of 0.1.…”
Section: Sequence Alignmentsmentioning
confidence: 99%
“…Several of the pleC suppressors displayed conditional cell division defects (9) and were mapped to divJ (5), which, like pleC (10), encodes a histidine protein kinase, and to divK (6), which encodes the first essential response regulator identified in bacteria. DivK is a 125-residue polypeptide that belongs to the subfamily of single-domain response regulators that includes the chemotactic protein CheY of Salmonella typhimurium (11) and the sporulation protein SpoOF of Bacillus subtilis (12). Although DivJ and DivK appear to play central roles in regulating initiation of cell division in C. crescentus (6), the PleC kinase may be more directly involved in regulating motility, chemotaxis, and stalk formation (13).…”
mentioning
confidence: 99%
“…There is no known function for the orfU gene product, and its deletion causes no observable change in phenotype (21). A similar open reading frame with 33% identity to orfU was reported for the Clostridium acetobutylicum glucitol operon, and its function is unknown (lla).…”
Section: Resultsmentioning
confidence: 99%
“…When these were compared with sequences in the data base, we found that the amino acid sequence matched the predicted sequence of the orfY-tsr gene, which maps close to spoOF (21); the sequence of orfYtsr, which apparently codes for fructose-1,6-bisphosphate aldolase (EC 4.1.2.13), has recently been revised (llb).…”
Section: Resultsmentioning
confidence: 99%